2019
DOI: 10.1111/jpy.12833
|View full text |Cite
|
Sign up to set email alerts
|

First description of the environmental niche of the epibenthic dinoflagellate species Coolia palmyrensis, C. malayensis, and C. tropicalis (Dinophyceae) from Eastern Australia

Abstract: Environmental variables such as temperature, salinity, and irradiance are significant drivers of microalgal growth and distribution. Therefore, understanding how these variables influence fitness of potentially toxic microalgal species is particularly important. In this study, strains of the potentially harmful epibenthic dinoflagellate species Coolia palmyrensis, C. malayensis, and C. tropicalis were isolated from coastal shallow water habitats on the east coast of Australia and identified using the D1‐D3 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
5
10
0
1
Order By: Relevance
“…The other three species, C. canariensis [28], C. santacroce and C. palmyrensis (present study), were found exclusively in offshore sites: Trindade Island for C. canariensis, Abrolhos Archipelago for C. santacroce and C. palmyrensis, and an offshore diving site in Pernambuco State for C. palmyrensis. Similar patterns of species distribution have been observed in Australia [22] and in the Iberian Peninsula [24], with C. malayensis more broadly distributed, C. tropicalis restricted to warmer waters, and C. palmyrensis present in offshore sites. Coolia santacroce, in turn, had only been recorded, so far, in the Caribbean Sea (GenBank sequences).…”
Section: Species Distribution and Diversity In Brazilsupporting
confidence: 74%
See 2 more Smart Citations
“…The other three species, C. canariensis [28], C. santacroce and C. palmyrensis (present study), were found exclusively in offshore sites: Trindade Island for C. canariensis, Abrolhos Archipelago for C. santacroce and C. palmyrensis, and an offshore diving site in Pernambuco State for C. palmyrensis. Similar patterns of species distribution have been observed in Australia [22] and in the Iberian Peninsula [24], with C. malayensis more broadly distributed, C. tropicalis restricted to warmer waters, and C. palmyrensis present in offshore sites. Coolia santacroce, in turn, had only been recorded, so far, in the Caribbean Sea (GenBank sequences).…”
Section: Species Distribution and Diversity In Brazilsupporting
confidence: 74%
“…Thus, a general pattern of Coolia spp. distribution seems to arise from this and previous studies: C. malayensis is globally distributed (see [14]); C. monotis is probably broadly distributed in coastal waters of Europe and the East Atlantic [24]; while distributions of C. tropicalis, C. canariensis, C. santacroce and C. palmyrensis are more restricted, mainly to warmer waters and/or to offshore sites with lower hydrodynamics (present study, [22]).…”
Section: Species Distribution and Diversity In Brazilsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, Coolia tropicalis has been found only in tropical waters of Malaysia to date (Leaw et al 2016). However, the C. tropicalis UTSHI1D5 strain isolated from Australia can survive in temperatures as low as 10°C (Table 8) (Larsson et al 2019). From 1984 to 2013, the average SST in the South Sea of Korea in February and December was more than 10°C and as high as 19°C around Jeju Island (Kwak et al 2015).…”
Section: Toxicitymentioning
confidence: 99%
“…Therefore, the occurrence of benthic dinoflagellates is a critical concern for scientists, government officers, and people in the aquaculture, dining, and tourism industries. Many benthic dinoflagellate species are distributed in tropical or subtropical waters, and fewer species occur in temperate waters (Besada et al 1982, Tindall and Morton 1998, Zingone et al 2006, Fraga et al 2008, Hallegraeff 2010, Leaw et al 2010, Glibert et al 2012, Parsons et al 2012, Larsson et al 2019, Pavaux et al 2020. However, the distribution of some benthic dinoflagellates living in tropic or subtropic waters has expanded into temperate waters owing to the elevated wa- Pavaux et al 2020.…”
Section: Introductionmentioning
confidence: 99%